Fabrication of Micro Ultrasonic Powder Molding Polypropylene Part with Hydrophobic Patterned Surface - Liang, Xiong (Materials (Basel), 2020)
Constructing regular micro-structures with certain geometric characteristics on the surface of the polymer part can obtain some specific functions. Micro ultrasonic powder molding (micro-UPM) is an efficient processing technique for the fabrication of well-filled micro-structured Polypropylene (PP) parts. The micro-structure array on the surface of the core insert was obtained by low speed wire electrical discharge machining (WEDM-LS). PP polymer surfaces with micro-structured patterns were successfully replicated from the core insert surface after micro-UPM. By studying the detailed topography characterizations of micro-structured PP parts, the effects of processing parameters (ultrasonic energy, welding pressure and holding time) on the micro-structured filling show that when PP polymer was formed under the conditions of 1000 J, 115 kPa and 8 s during micro-UPM, well-filled micro-structured parts can be obtained. Besides, without low surface energy coating modification, the water contact angles (WCAs) of micro-structured PP parts increased from 85.3° to 146.8°, indicating that the wettability of the surface can be changed by replicating the micro-structure on PP parts after micro-UPM.